(untitled) (Legislatif, 2020)
Abstract To find out the strengthening of the customary rights of ammatoa kajang through the protection of the existence of customary forests in national regulations and legislation and to find out the legal consequences of the decision Mahkamah Konstitusi Number 35/PUU-X/2012 on the existence of customary forests. Protection of customary forests in legislation cannot be separated from the recognition of the customary law community first. In the legislation has become a challenge for the existence of indigenous peoples, Pasal 18B Ayat 2 UUD 1945 became the basis for the protection of the community the customary law stipulated in the Regional Regulations recognizing customary law communities, Pasal 67 Ayat 2 UU No. 41 About Forestry. With public awareness of the functions of forests, the Ammatoa customary law community will always maintain the forest sustainability. If not, they themselves will feel the consequences. There will be drought and crop failure, and will not be able to carry out other activities which are always explained by them "life will be destroyed" in the Pasang ri kajang a rule that still exists today. Through the Decision of the Mahkamah Konstitusi No.35/PUU-X/2012 by the Regional Government and related Institutions along with the DPRD in Bulukumba Regency and the Ammatoa customary law Society, jointly design the Regional Regulations for the Recognition of Customary Law Communities to protect the existence of Ammatoa indigenous peoples’ rights including the customary forest. Keywords: Custo`mary rights; customary forests; customary law communities ammatoa kajang; Abstrak Untuk mengetahui penguatan hak-hak adat ammatoa kajang melalui perlindungan terhadap eksistensi hutan adat dalam peraturan dan perundangan nasional serta untuk mengetahui akibat hukum yang ditimbulkan putusan Mahkamah Konstitusi Nomor 35/PUU-X/2012 terhadap eksistensi hutan adat. Dalam peraturan Perundang-Undangan telah menjadi tantangan bagi eksistensi masyarakat hukum adat, Pasal 18B Ayat (2) UUD 1945 menjadi dasar bagi perlindungan eksistensi masyarakat hukum adatnya yang diatur di dalam Peraturan Daerah pengakuan masyarakat hukum adat, sebagaimana pasal 67 Ayat (2) UU No. 41 Tentang Kehutanan. Dengan kesadaran masyarakat akan fungsi hutan, masyarakat hukum adat Ammatoa akan senantiasa menjaga kelestrian hutan. Jika tidak, mereka sendiri yang akan merasakan akibatnya. Akan terjadi kekeringan dan gagal panen, serta tidak dapat menjalankan aktivitas lainnya yang selalu dibahasakan oleh mereka “kehidupan akan hancur” dalam Pasang ri kajang sebuah aturan yang sampai saat ini masih eksis. Melalui Putusan Mahkamah Konstitusi No.35/PUU-X/2012 oleh Pemerintah Daerah dan Instansi terkait beserta DPRD di Kabupaten Bulukumba dan Masyarakat hukum adat Ammatoa, bersama-sama merancang Peraturan Daerah Pengakuan Masyarakat Hukum Adat untuk melindungi eksistensi hak-hak masyarakat hukum adat Ammatoa termasuk hutan adatnya. Kata Kunci : Hak adat; Hutan adat; Masyarakat Hukum adat ammatoa kajang;